Nebesna Sotnia: Formation of a New Narrative from Protest Lore to Institutionalized Commemorative Practice - Bezborodova, Nataliya (Ethnologies, 2018)
The one hundred people shot dead on the Maidan were given the collective name Heavenly Hundred (Nebesna Sotnia). It became the central memory of the uprising; a hymn, a new state award, a national memorial day, poetry, monuments, memorial plaques and books were produced. Dozens of streets and squares were renamed in different regions.The paper focuses on the interpretations of large-scale historical events (the Cossack, the Ukrainian National Republic and World War II), and their incorporation into a new institutionalized narrative after drastic societal events on the example of the protests in Ukraine known as the Maidan in the winter of 2014. The research is based on original protest lore, 8905 Facebook posts from 1647 individuals, collected by the author on the day they were published on Facebook between January 19 – February 28, 2014. This timeframe includes both peaceful days and the most dramatic confrontation of the protests. The data originally was organized in 5 categories and 16 topics.The paper provides evidence of how personal stories function and validate the participants’ experiences and the significance of the events from the protestors’ perspectives; and protest lore impact on institutional changes of commemorative practices in the field of collective memory.